Conflict Management Effectiveness: A Case Study in Determining the Status Quo of Sultan Suriansyah's Tomb in Indonesia - Siti Hamidah; Rizky Kursiah; Safa Muzdalifah (International Journal of Southeast Asian Studies (IJSAS), 2022)
Abstract— The conflict of the Tomb of the Sultan of Suriansyah is a conflict that has been going on for quite a long time. This conflict occurred between two families who felt they had a right of management of the tomb. Therefore, the study aims to describe the effectiveness of conflict management that has been carried out by related parties, namely local governments. The method used in this study is a qualitative method, with a descriptive type.The key informants in this study were the Head of the Archaeological Development & Cultural Heritage Section of the Banjarmasin City Culture and Tourism Office, the Manager of the Tomb of Sultan Suriansyah, and the community. Data collection techniques use tringulation techniques, starting from observation, interviews, and documentation. Data analysis in this study consists of: data reduction, data presentation and conclusions or verification. The results of this study state that the conflict management carried out uses an integrative model, an interactive model, a stimulus model and a conflict reduction model. The role of the Banjarmasin City Government in resolving the conflict between the tomb of Sultan Suriansyah is still not optimal. Finally, the decision to resolve the conflict was taken over by the North Banjarmasin Police Chief. The goal is to narrow the scope of the conflict.